SOCIAL ENTREPRENEURSHIP AND ITS BUSINESS MODELS IN FOOD INDUSTRY - Tran, Nghi Luc (My University, 2018)
The objective of the thesis is to understand social entrepreneurship phenomenon in the food industry and how it generates values for individuals, local communities, and society. The phenomenon is known as a sustainable method that can solve social problems. However, research on social entrepreneurship is more in general from different sectors and regions. Thus, studying in a particular context – food industry to find out what values food social enterprises create and how their business models operate would contribute another perspective for the academy world and provide practices for social entrepreneurs in food industry. A literature review describes central concepts to provide a fundamental knowledge of social entrepreneurship, business model and value creation emphasizing economic and social values. The study uses qualitative content analysis with a case of a non-profit organization (NGO) and theme in-depth interviews conducted with six social entrepreneurs from Southeast Asia and Africa. The findings indicate that innovation, network and human resource play an important role in social business models to generate values for farmers, consumers, and local communities.
Keywords: Social entrepreneurship; Social enterprises; Social ventures; Food Industry; Value creation; Business Model; Business Model Canvas; fi=Markkinointi|en=Marketing|; fi=Master's Degree Programme in International Business|